2018
DOI: 10.1371/journal.pone.0196363
|View full text |Cite
|
Sign up to set email alerts
|

Underlying mechanism of subcortical brain protection during hypoxia and reoxygenation in a sheep model - Influence of α1-adrenergic signalling

Abstract: While the cerebral autoregulation sufficiently protects subcortical brain regions during hypoxia or asphyxia, the cerebral cortex is not as adequately protected, which suggests that regulation of the cerebral blood flow (CBF) is area-specific. Hypoxia was induced by inhalation of 5% oxygen, for reoxygenation 100% oxygen was used. Cortical and subcortical CBF (by laser Doppler flowmetry), blood gases, mean arterial blood pressure (MABP), heart rate and renal blood flow were constantly monitored. Low dosed urapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We confirmed the dichotomy of cortical and subcortical CBF in control animals during hypoxia ( Figure 4A) [19]. The subcortical CBF increased over the course of hypoxia, whereas the cortical CBF decreased in comparison to baseline values (both p < 0.001), resulting in a significant difference in CBF between the two brain regions (p < 0.05).…”
Section: Int J Mol Sci 2020 21 X For Peer Review 4 Of 22supporting
confidence: 81%
See 1 more Smart Citation
“…We confirmed the dichotomy of cortical and subcortical CBF in control animals during hypoxia ( Figure 4A) [19]. The subcortical CBF increased over the course of hypoxia, whereas the cortical CBF decreased in comparison to baseline values (both p < 0.001), resulting in a significant difference in CBF between the two brain regions (p < 0.05).…”
Section: Int J Mol Sci 2020 21 X For Peer Review 4 Of 22supporting
confidence: 81%
“…Sheep were elected as the experimental model for our studies because of their similarities to humans, including body weight, physiological parameters, and organization of the brain. Using this model, we have previously shown that hemorrhage [20] or hypoxia [19], respectively, trigger differential CBF responses in the cortex and subcortex. Both damage models resulted in lower cortical CBF in comparison with subcortical CBF, which was replicated in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is now considerable evidence that fetal cerebral redistribution is associated with adverse outcomes, including perinatal death, even in appropriately grown fetuses [ 29 , 54 , 55 , 56 ]. In animal models, it has been proposed that the regulation of cerebral blood flow is area-specific, with some areas more prone to cerebral injury in the event of a hypoxic event [ 57 , 58 ]. It has also been proposed that fetal brain injury may actually be initiated as a consequence of cerebral redistribution, with increased flow as a particular risk factor [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that CBF response to hypoxia is brain area-specific. 78 During hypoxia (5% O 2 ), subcortical brain regions showed a high protection mechanism through cerebral autoregulation, but in the cerebral cortex the protection mechanism failed and CBF decreased with hypoxia. 78 Mild and severe hypoxia induced by reducing S a O 2 resulted in a reduction in cellular oxygen availability.…”
Section: The Effect Of Hypoxia On Cbf and Cco Oxidation Statementioning
confidence: 99%